Ikonisitas Tata Panggung: Sebuah Kajian Semiotika Seni Rupa Teater - UNTUNG TRI BUDI ANTONO (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2008)
The Semiotic of Stage. Semiotics is a study dealing with signs and sign systems. Signs are created for theneeds of communication and information. According to Piercean’s, semiotics in theatre is a transformation of storysigns which symbolically become iconic signs of its acts. Stage setting is an artistic part of theatre which makes usethe potentials of iconicity. Since its functions as a drama support of the acts, its potentials of iconicity optimize itsfunctions.